Evolution of Muslim personal law in the South African constitutional dispensation - Abduroaf, Sheikh Muneer (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This paper was presented by a representative of the Muslim Judicial Council, South Africa.  The paper is about the evolution of Muslim personal law in the South African Constitutional dispensation. This paper looks at the advancements of Muslim personal law in the South African courts, and also the advancements as regards to statute law.